Spectroscopic (FT-IR, FT-Raman, 1H and 13C NMR) and theoretical studies of p-coumaric acid and alkali metal p-coumarates. Issue 1 (2012) - Świsłocka Świsłocka, Renata Renata; Kowczyk-Sadowy Kowczyk-Sadowy, Małgorzata Małgorzata; Kalinowska Kalinowska, Monika Monika; Lewandowski Lewandowski, Włodzimierz Włodzimierz
Abstract : The evaluation of the electronic charge distribution in metal complexes enables more precise interpretation of mechanism by which particular metal ions affect biochemical properties of ligands [J. Inorg. Biochem. 99 (2005), 1407–1423, J. Mol. Struct. 919 (2009), 284–289]. In this paper we investigated the influence of alkali metal cations (lithium, sodium, potassium, rubidium and cesium) on the electronic structure of p -coumaric acid ( p -CA). It allowed to observe the systematic changes in the spectra of investigated complexes depending on the position of the element in the periodic table. p -Coumaric acid is a derivative of cinnamic acid that occurs in several plant species. Li, Na, K, Rb and Cs p -coumarates were synthesized and the experimental and theoretical FT-IR, FT-Raman, 1 H and 13 C NMR spectra of p -coumaric acid and its salts were registered and analyzed. The structures, atomic charges, infrared and NMR spectra of p -coumaric acid and Li, Na, K salts were calculated by B3LYP/6-311++G ** method.